Comparative study of phytochemical content and bioactivity of five Zingiberaceae species from Thailand with biodiversity implications - CHANAKRAN PAPAYRATA; SURAPON SAENSOUK; THEERAPHAN CHUMROENPHAT (Society for Indonesian Biodiversity, 2025)
Abstract. Papayrata C, Saensouk S, Chumroenphat T. 2025. Comparative study of phytochemical content and bioactivity of five Zingiberaceae species from Thailand with biodiversity implications. Biodiversitas 26: 4229-4242. Zingiberaceae plants are widely used in traditional medicine and as food ingredients. Their phytochemicals and biological activities differ depending on species, genotype, and cultivation conditions. This study investigated five Thai Zingiberaceae species, including Zingiber chrysostachys (ZC), Zingiber niveum (ZN), Zingiber ligulatum (ZS), Alpinia galanga white cultivar (AGW), and yellow cultivar (AGY). ZC showed the highest total phenolic content (200.04 mg GAE/100 g DW) and total flavonoid content (157.16 mg RE/100 g DW), with myricetin at a concentration of 146.14 µg/g DW. Caffeic acid was the major phenolic acid found in all species, with the highest concentration in ZN (109.60 µg/100 g DW). ZC exhibited the highest antioxidant activity with a DPPH scavenging activity of 471.77 µg TE/g DW, IC50 of 251.04 µg/mL, and 104.71 mmol FeSO?/g DW by FRAP assay, with AGE inhibition of 98.15%. AGY was prominent for its remarkably high curcumin content (263.42 µg/g DW), ZN contained the highest 6-gingerol (118.37 µg/g DW), AGW had the highest eugenol concentration (17.92 µg/g DW), and ZS showed the highest vitamin C content (16.29 mg/100 g DW). Multivariate analyses confirmed strong correlations between myricetin, caffeic acid, and rutin, as well as their corresponding biological activities. ZC demonstrated the best potential for development as a functional food or herbal ingredient.